2013
DOI: 10.2967/jnumed.113.129411
|View full text |Cite
|
Sign up to set email alerts
|

“To Serve and Protect”: Enzyme Inhibitors as Radiopeptide Escorts Promote Tumor Targeting

Abstract: Radiolabeled octreotide analogs are most successfully being applied today in clinical cancer imaging and treatment. Propagation of this paradigm to other radiopeptide families has been greatly hampered by the inherent poor metabolic stability of systemically administered peptide analogs. We hypothesized that the in vivo coadministration of specific enzyme inhibitors would improve peptide bioavailability and hence tumor uptake. Through single coinjection of the neutral endopeptidase inhibitor phosphoramidon (PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
167
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 104 publications
(180 citation statements)
references
References 32 publications
11
167
2
Order By: Relevance
“…Regarding stability in the bloodstream, peptide molecules are known to be vulnerable to degradation by peptidases (30). Nonetheless, radiolabeled DTPA-and DOTA-linked Tyr 3 -octreotide and Tyr 3 -octreotate have exhibited excellent stability in circulation; they are excreted via the urine mostly in the intact form (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding stability in the bloodstream, peptide molecules are known to be vulnerable to degradation by peptidases (30). Nonetheless, radiolabeled DTPA-and DOTA-linked Tyr 3 -octreotide and Tyr 3 -octreotate have exhibited excellent stability in circulation; they are excreted via the urine mostly in the intact form (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, radiolabeled DTPA-and DOTA-linked Tyr 3 -octreotide and Tyr 3 -octreotate have exhibited excellent stability in circulation; they are excreted via the urine mostly in the intact form (30)(31)(32). Therefore, we expect our hybrid Cy5-111 In-DTPA-Tyr 3 -octreotate peptide analog to exhibit good stability in circulation as well.…”
Section: Discussionmentioning
confidence: 99%
“…A remarkable advance in this area is the discovery of the in vivo enzyme inhibition concept, in which radiopeptides are administered together with an enzyme inhibitor as a safeguard against enzymatic degradation. It has recently been shown that coinjection of a neutral endopeptidase inhibitor, such as phosphoramidon, can stabilize radiolabeled bombesin, minigastrin, and somatostatin analogs in vivo, leading to enhanced tumor uptake and improved tumor visualization (5). We believe that this strategy will have a significant impact on patient care, as it may enhance the diagnostic sensitivity and therapeutic efficacy of radiopeptides.…”
Section: Improving Pharmacokinetics and In Vivo Stabilitymentioning
confidence: 98%
“…neutral endopeptidase, NEP) is responsible for the rapid in vivo breakdown of intravenously administered radiopeptides from at least the somatostatin, bombesin, and gastrin peptide families. Most importantly, this phenomenon can be overcome by enhan cing their supply and accumulation at tumor sites through the mere co-injection of a protease inhibitor, such as phosphoramidon [69]. This approach may result in increased diagnostic sensitivity and therapeutic efficacy being the potential strategy for translation into clinical practice [70,71].…”
mentioning
confidence: 99%